Turkey : Staff Report for the 2010 Article IV Consultation and Post; Program Monitoring-Supplementary Information; Staff Report; Informational Annex; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
On the eve of the global financial crisis, the Turkish economy had just concluded a six-year growth surge, spurred by policy reforms and favorable external and domestic conditions. Turkish GDP was hit hard by the onset of the global financial crisis, but quickly retraced its losses. The authorities' macroeconomic policy response to the severe GDP contraction was broadly appropriate in timing and magnitude and made feasible by the previously conservative stance of policies. Executive Directors underscored the need for bold structural reforms.